Стан розвитку підприємництва в Україні та Дніпропетровському регіоні - Дундук, В.Н.; Михальчук, Л.В. (Культура народов Причерноморья, 2013)
У статті досліджено особливості діяльності малого підприємництва в Україні та
Дніпропетровському регіоні за 2006-2010 рр. Проведено аналіз статистичних даних основних показників
діяльності малих підприємств і фізичних осіб-підприємців. Проілюстровано невідповідність відносної
кількості зайнятих працівників до частки внеску малого підприємництва в загальний обсяг реалізованої
продукції (робіт, послуг).
Виконано аналіз динаміки основних показників розвитку малих підприємств в Дніпропетровській
області. Зроблені висновки щодо напрямків покращення умов діяльності та розвитку малого бізнесу в
Україні.
Ключові слова: малі підприємства, фізичні особи-підприємці, показники діяльності, зайняті працівники,
реалізація продукції, розвиток малого бізнесу, причини, що протидіють розвитку. В статье исследованы особенности деятельности малого предпринимательства в
Украине и Днепропетровском регионе за 2006-2010 гг. Проведен анализ статистических данных
основных показателей деятельности малых предприятий и физических лиц-предпринимателей.
Проиллюстрировано несоответствие относительного количества занятых работников к доле взноса
малого предпринимательства в общий объем реализованной продукции (работ, услуг).
Выполнен анализ динамики основных показателей развития малых предприятий в Днепропетровской
области. Сделанны выводы относительно направлений улучшения условий деятельности и развития
малого бизнеса в Украине.
Ключевые слова: малые предприятия, физические лица-предприниматели, показатели деятельности,
занятые работники, реализация продукции, развитие малого бизнеса, причины противодействия
развитию. The article observes the characteristics of small business in Ukraine and Dnipropetrovsk region in
2006-2010. The analysis of statistical data of key indicators of small businesses and individual entrepreneurs on
key indicators of small businesses (regardless of ownership) and individual entrepreneurs on the criteria set out
in the Commercial Code of Ukraine of 18.09.2008 as amended, which states that the situation in the
development of small businesses is close to the unsatisfactory. Small businesses and individual entrepreneurs
make a little contribution to the national economy.
Illustrated discrepancy of a number of employees to the contribution of small business in the total sales of goods
(works, services).
One of the most developed industrial regions near Dnieper is the Dnipropetrovsk region. In Dnepropetrovsk
almost one-fifth of all industrial production in Ukraine is produced. The analysis of the main indicators of small
businesses in the Dnipropetrovsk region shows that in this region there are also problems in small business.
Conclusions about improvement of small business in Ukraine are made and comprehensive measures by the
state to convert to a favorable market environment for business development are implemented.
Keywords: small businesses, individual entrepreneurs, performance, employers, sales, small business
development, reasons for opposing the development.